The Downfall of the American Order? - Kirshner, Jonathan; Katzenstein, Peter J. (Book collections on Project MUSE., 2022)
"The American-led international order, forged after the end of the Second World War, appears to have come to an end. This book of essays examines the character of the American order and considers the implications of what might come next, with an emphasis on the prospects for liberalism, broadly defined" --